Roadmap for Safer Schools - World Bank (World Bank, Washington, DC, 2017)
Each year countries suffer great tragedy when natural disasters destroy schools and disrupt children’s education. In addition to causing immediate harm to children, there is mounting evidence that the direct impact of natural disasters can translate into a series of indirect long-term effects. For some time, multilateral and bilateral development finance institutions, United Nations (UN) agencies, and nongovernmental organizations (NGOs) have been engaged in efforts to make schools resilient to natural hazards. Despite these efforts, however, the safety of school facilities in many disaster-prone countries is unknown, and governments and donors continue to finance new school construction without taking sufficient account of safety. In 2014, the Global Facility for Disaster Reduction and Recovery (GFDRR) launched the Global Program for Safer Schools (GPSS). Through the GPSS, GFDRR support programs designed to establish safer school facilities in countries where the government has firmly committed to a reform or investment program in the education sector. GFDRR provides technical assistance to ensure that such education sector programs finance safer school facilities. The aim of the GPSS is to make school facilities, and the communities they serve, more resilient to natural hazards. This Roadmap is focused specifically on school infrastructure (which includes the school site and buildings). For investment opportunities to be effective and to have maximum impact at community and national scales, it is important that this support is coordinated with investments in school disaster management, risk reduction and resilience in education, and disaster preparedness in other sectors.